Knockdown of LINC01116 inhibits cell migration and invasion in head and neck squamous cell carcinoma through epithelial‐mesenchymal transition pathway. Issue 1 (26th August 2019) - Wu, Jing; Chen, Zhizhao; Zhang, Li; Cao, Jun; Li, Xiaoyu; Gong, Zhaojian; Bo, Hao; Zhang, Shanshan; He, Dong
Abstract: Long noncoding RNAs (lncRNAs) are linked to tumor development and progression. The aim of this study was to determine the prognostic significance and biological role of LINC01116 in head and neck squamous cell carcinoma (HNSCC). We identified 21 aberrantly expressed lncRNAs specific to HNSCC that were common in two microarray datasets. LINC01116 was highly overexpressed in HNSCC tissues and was correlated to shorter overall survival and relapse‐free survival duration, as analyzed by the online Gene Expression Profiling Interactive Analysis platform. LINC01116 was also overexpressed in oral squamous cell carcinoma and nasopharyngeal carcinoma tissues, and LINC01116 silencing significantly inhibited the migration and invasion capacities of both cell lines by blocking the epithelial‐mesenchymal transition process. In addition, 125 coexpressing genes were identified by circlncRNAnet, and were mainly located on human autosomes and enriched in transforming growth factor‐β signaling pathway. These findings indicate that LINC01116 might be a potential therapeutic target for HNSCC. Abstract : LINC01116 was highly expressed in head and neck squamous cell carcinoma. LINC01116 silencing inhibited the migration and invasion capacities of the tumor cells. LINC01116 regulated the tumor function through epithelial‐mesenchymal transition process (EMT).